Bioethanol from olive residues: prospects for a large scale production in the south of Algeria - Benoumhani, Sofiane (International Journal of Psychosocial Rehabilitation, 2020)
— in the south-east of Algeria, olive cultivation and olive oil production know a remarkable development. But, the waste resulting from the olive oil industry represents a supplementary charge. Many ways used to valorize these residues such as livestock nutrition, solid fuel and ethanol extraction. In this context, the development of olive production in the southern regions (Ouargla and Ghardaia provinces) is examined. The geographical information system “ArcGIS” software is used to evaluate the natural potential of solar radiation, precipitation, groundwater reserves and large plains in these areas. The solar radiation lies between 5.3 and 6.5 KWh/m2. By eliminating undesired zones which contain habitation and activity zones, sand and rocky soil, mountains, lacks and valleys, the available plain are evaluated at 15180 x103 hectares which present about 52 % of two provinces total area. The intersection of superposing maps (soil, precipitation and groundwater depth) gives the suitable areas for olive tree cultivation which can reach 5190 103 hectares. The obtained results show that the extension of olive cultivation is very promoting. In 2015, this agriculture covers 2471 hectares and releases 5500 x103 kg as residues. By using latest research rate of ethanol extraction, producing ethanol from olive residues is estimated at 1466 x103 liters. In 2040, the voluntary model shows that cultivated areas, olive residues and bio-ethanol production can reach 48800 hectares, 1086141 x103 kg and 22840 x103 liters respectively. For initial small scale bio-ethanol production, the cost evaluating shows that it remains relatively high (210.41 DZA (1.68 €) per litter.